Proceedings of the Ninth Biennial ACM Symposium on Eye Tracking Research &Amp; Applications 2016
DOI: 10.1145/2857491.2857519
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking scanpath analysis on web pages

Abstract: The number of users required for usability studies has been a controversial issue over 30 years. Some researchers suggest a certain number of users to be included in these studies. However, they do not focus on eye tracking studies for analysing eye movement sequences of users (i.e., scanpaths) on web pages. We investigate the effects of the number of users on scanpath analysis with our algorithm that was designed for identifying the most commonly followed path by multiple users. Our experimental results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…Usability experiments using goal-directed searching tasks require a smaller sample than undirected browsing. Representative scan paths may be determined for search tasks using 27 participants (Eraslan, Yesilada, & Harper, 2016). A metaanalysis of eye-tracking research on differences between experts and novices found an average cell size of 11.…”
Section: Key Data Measuresmentioning
confidence: 99%
“…Usability experiments using goal-directed searching tasks require a smaller sample than undirected browsing. Representative scan paths may be determined for search tasks using 27 participants (Eraslan, Yesilada, & Harper, 2016). A metaanalysis of eye-tracking research on differences between experts and novices found an average cell size of 11.…”
Section: Key Data Measuresmentioning
confidence: 99%
“…It is obvious that the video recording would suffer significantly once the dataset becomes larger, i.e., for large scale usability study with many users. Some of the recent studies have shown that Web usability studies would require at least 27 users for searching tasks and 34 users for browsing tasks [Eraslan et al 2016], which emphasizes the potential of the enhanced representation method in real-world applications. Furthermore, with the evolution of cheap eye trackers, the user-base is expanding, and there is an increasing interest for Web page usability analysis using crowd-sourcing [Lebreton et al 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, analysts must analyze the video of each user one by one to understand all the effects of the interface design, making the analysis time-consuming and tedious. In general, this is not a scalable solution, because usability analysis requires feedback from a reasonable number of users [Eraslan et al 2016].…”
Section: Introductionmentioning
confidence: 99%
“…The study entailed registering the eyeball movement of individual observers looking out at the test landscape during each season of the year under selected weather types that positively or negatively impacted each participant. In the author's opinion, the numerical composition of the test group was sufficient for eye tracking research, similar to psychophysiology studies that require a smaller sample, and in general even fewer participants, for example, 20-30 participants can be considered representative [72,73].…”
Section: Ffd (First Fixation Duration)mentioning
confidence: 99%